(untitled) (Revista de Diavulgación L’esprit Ingénieux, 2021)
The editorial committee of the student magazine L’esprit Ingénieux of the Faculty of Civil Engineering of the Universidad Santo Tomás Tunja, is pleased to present the volume 11 No 1 2020. This journal aims to disseminate research articles and / or review, graduate work, results of research workshops and products of classroom work developed by the student community with the support and co-authorship of the teachers of our faculty. The publication of this volume has been possible thanks to the efforts of teachers, students and administrators who are an integral part of this process. Students find in this journal, an opportunity to present their work to the national and international community, allowing the strengthening of their reading, writing and research skills, also contributing to the substantive functions of teaching, social projection and research of the Faculty of Civil Engineering. Volume 11 2020 of the journal L’esprit Ingénieux, has materialized thanks to the research proposals of the students that include the different areas of knowledge of civil engineering. These research proposals are based on the solution of local, regional and/or national problems, incorporating a component of social projection towards the communities and environmental responsibility that aim at strengthening the fulfillment of the objectives of sustainable development and actions that also allow to face climate change. Thus, the objectives of the journal are articulated with the thematic focuses of the 2019 mission of wise men and women, the Departmental strategic plans in science, technology and innovation, the national development plan 2018-2022 and the comprehensive multicampus plan of Universidad Santo Tomás Colombia (PIM, 2016 - 2027). Volume 11 2020 consists of five articles covering different topics including environmental education, geology, satellite imaging, reuse of construction waste and optimization of coagulation processes for drinking water production. The first article describes an environmental education project with social responsibility, which involves an integrated work with communities, schools and colleges in the city of Tunja, materializing pedagogical strategies that account for the conservation and care of the environment by reducing the generation of urban solid waste. To this end, activities and campaigns were carried out for the selection, classification and final disposal of solid, organic, toxic and hospital waste, avoiding its direct disposal into the environment and preventing contamination of water sources, soil and air. The project counted with the participation of Universidad Santo Tomás Tunja as promoter of this initiative. In article number two, the students propose the development of a flowchart that allows the creation of a geological profile through the use of specialized software such as QGIS and a computer-assisted drawing program such as AutoCAD. The use of these technological tools is an integral part of the different syllabuses conceptualized in the different academic areas of the Civil Engineering program and their potential uses are materialized in this article. In a third article, a current topic of general interest for civil, sanitary, environmental and cadastral engineers is presented, such as the processing of satellite images. In this research, students present the Landsat system for the acquisition of high-resolution satellite images of the earth’s surface. The article describes in detail the methodology for the processing of this type of images incorporating the use of specialized software such as Erdas Imagine and ArcGIS. The result of this methodology will also allow determining the type of land cover and land use in a given area, which can be evaluated and monitored to establish its change over time, evidenced for example by the loss of forest areas, with consequences of desertification of key areas for agriculture and/or grazing activities. In the fourth article, the students focus their research on the impact generated by the inadequate disposal of demolition and construction waste, which in many cases are disposed of in inappropriate areas such as the so-called dumps, in which these wastes are disposed of in the open air, generating particulate matter pollution in the air, contributing solids to water sources and producing a negative visual impact on the landscape. For this reason, the research is directed towards the analysis and characterization of these wastes from the morphological, physical, chemical and mineralogical point of view, concluding that these materials can be recycled and reused through their transformation and addition in the creation of new products for the construction of infrastructure works. Finally, in this volume we find an article whose main theme focuses on the optimization of coagulation processes treating water from the Ottawa River in Canada, for the production of drinking water. This article is a product of preliminary laboratory tests in the development of a doctoral thesis of a professor of our Faculty at the University of Ottawa, Canada. The research was financially supported by the Universidad Santo Tomás Tunja, COLCIENCIAS and COLFUTURO, Colombia through the scholarship for doctoral studies abroad. This article may be used by teachers in the area of water and environmental resources as reinforcement and support for the topics found in the different academic areas of the Civil Engineering program. We reiterate again with this new volume the invitation to the entire academic community of the Universidad Santo Tomás Colombia, to send us their work and continue strengthening the seed of research in our future professionals because as an Arab proverb says ¨Who wants to do something finds a way, who does not want to do anything finds an excuse¨.